TRANSFORMASI PENDIDIKAN KARAKTER INKLUSIF: STRATEGI GURU DALAM MENUMBUHKAN SIKAP BERBAGI PADA ANAK USIA DINI - Aprilia Kartika Sari; Talitha Najma Nadifah; Amalia Nazala Ruzda; Siau Ling; Dea Ayu Febriana; Naely Nafisah; Ningsih Fadhilah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social-emotional development is a fundamental aspect for early childhood to build positive relationships, although challenges such as egocentric traits that make children reluctant to share are still often encountered. Through a descriptive qualitative approach at Muslimat NU Kindergarten in 2026, this study revealed that these obstacles can be overcome through consistent stimulation of prosocial behavior, where teachers implement various pedagogical strategies such as habituation, providing role models, interactive storytelling, role-playing methods, and cooperative activities such as eating together. Success in cultivating this value of sharing does not only rely on the role of teachers in the classroom, but also depends heavily on close collaboration between schools and parents through ongoing communication and supportive parenting programs. Overall, harmonious synergy between the educational environment and the family is the main key so that the values ​​of caring can be internalized and become real habits in children's daily lives.